FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TAHU PUTIH DI KOTA MEDAN - M. Fahriza Ikhsan; Retna Astuti K; Faoeza Hafiz Saragih (Universitas Medan Area, 2019)
Tofu is one of the foodstuffs that plays a role for nutritional balance and is one of the people's favorite side dishes. The purpose of this study is to find out what factors influence consumer demand for white tofu in the city of Medan. The sampling method is done by purposive sampling method. Respondents in this study were consumers who consumed white tofu in the household. Information obtained from white tofu sellers in Petisah Market, Sei Sikambing Market and Helvetia Market and samples taken were 45 respondents, each 15 respondents in each market. Data collected are primary data and secondary data. The analytical method used is multiple linear regression test with SPSS 20. The results of this study concluded that the variable price of white tofu, tempe prices, fish prices, income and the number of dependents simultaneously had a significant effect on the demand for white tofu in Medan. Partially the variable price of white tofu and fish prices has a significant effect on the demand for white tofu in Medan, while the variable price of tempe, income and the number of dependents does not significantly influence the demand for white tofu in Medan.